Fostering Positive Learning Attitudes on Aqidah Akhlak subject through Self-directed learning: A Study at MTs Nurul Hidayah Yanuhi Lewisadeng Bogor (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study explores the implementation of self-directed learning (SDL) in Aqidah Akhlak instruction at MTs Nurul Hidayah and its influence on students’ learning attitudes and character development. The research was conducted using a qualitative case study approach through in-depth interviews with teachers and students. The findings reveal that SDL promotes increased student independence, responsibility, interest, and enthusiasm, while also encouraging positive behavioral changes aligned with the values taught in Islamic education. The integration of digital tools was found to support students' autonomy and improve their engagement, particularly in a suburban school context with limited resources. The study highlights that SDL, typically studied in higher education, can be effectively applied to junior high school settings to foster both cognitive and moral development. These results offer practical implications for improving Islamic religious education and contribute to the growing discourse on SDL in secondary education. Limitations include the single-site focus and qualitative design; therefore, future research should consider broader comparative and quantitative approaches to enrich the understanding of SDL’s impact across various educational environments.